ANALISIS PENERAPAN ARSITEKTUR INDUSTRIAL PADA TOKO OLAHRAGA (STUDI KASUS: DECATHLON SUMMARECON, KOTA BEKASI) - Muhammad Rizky Fadillah; Tuntun Rahayu (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2024)
Industrial architecture has become a trend in commercial building design, including retail stores. This style emphasizes elements such as exposed structures, raw materials, and functional aesthetics. This study aims to analyze the application of industrial architecture in the Decathlon Summarecon sports store in Bekasi City and identify the key elements used in its implementation. The research method used is qualitative descriptive with a literature study approach and visual observation of design elements. The results show that the application of industrial architecture in this store is evident from the use of exposed materials such as concrete, steel, and wood, an open structure that creates a spacious impression, and exposed mechanical elements that reinforce the industrial character. Additionally, the choice of natural colors in the materials provides an authentic and functional impression. This study offers insights for architects and interior designers in adapting the concept of industrial architecture to other retail stores to enhance their appeal